Moderate threat causes longer lasting disruption to processing in anxious individuals - Forster, Sophie; Nunez-Elizalde, Anwar O.; Castle, Elizabeth; Bishop, Sonia J. (Frontiers in Human Neuroscience, 2014)
Anxiety is associated with increased attentional capture by threat. Previous studies have used simultaneous or briefly separated (< 1s) presentation of threat distractors and target stimuli. Here, we tested the hypothesis that high trait anxious participants would show a longer time window within which distractors cause disruption to subsequent task processing, and that this would particularly be observed for stimuli of moderate or ambiguous threat value. A novel temporally separated emotional distractor task was used. Face or house distractors were presented for 250ms at short (~1.6s) or long (~3s) intervals prior to a letter string comprising Xs or Ns. Trait anxiety was associated with slowed identification of letter strings presented at long intervals after face distractors with part surprise / part fear expressions. In other words, these distractors had an impact on high anxious individuals’ speed of target identification seconds after their offset. This was associated with increased activity in the fusiform gyrus and amygdala and reduced dorsal anterior cingulate recruitment. This pattern of activity may reflect impoverished recruitment of reactive control mechanisms to damp down stimulus-specific processing in subcortical and higher visual regions. These findings have implications for understanding how threat-related attentional biases in anxiety may lead to dysfunction in everyday settings where stimuli of moderate, potentially ambiguous, threat value such as those used here are fairly common, and where attentional disruption lasting several seconds may have a profound impact.